Merging radical-polar crossover/cycloisomerization processes: access to polyfunctional furans enabled by metallaphotoredox catalysis. Issue 8 (10th February 2021) - Liu, Yongjun; Luo, Wenping; Xia, Tingting; Fang, Yewen; Du, Chan; Jin, Xiaoping; Li, Yan; Zhang, Li; Lei, Wan; Wu, Hao
Abstract : Metallaphotoredox catalysis for furan synthesis: The cyclisation of yne-enones proceeds smoothly via consecutive reductive radical-polar crossover and cycloisomerization processes enabled by cooperative photoredox-neutral and copper catalysis. Abstract : With the radical derived from alkyl silicates or 4-alkyl-1, 4-dihydropyridines as the surrogate for the nucleophile, the cyclisation of 2-(1-alkynyl)-2-alken-1-ones proceeds smoothly via consecutive reductive radical-polar crossover and cycloisomerization processes enabled by dual photoredox–copper catalysis. Both single-electron oxidation and reduction occur between the photocatalyst and radical precursor/adduct radical, generating the enolate ion without the need for a base and an exogenous oxidant–reductant. In contrast to the reported transition-metal catalysed cyclisation with the oxonium ion as the key intermediate, the nucleophilic attack of enolate-oxygen on the copper coordinated alkyne was proposed for this dual catalysis. This new methodology for the preparation of polyfunctional furans features mild conditions, a broad substrate scope, and good functional group tolerance.